Relationship Between Desk Chair Workstations and the Incidence of Low Back Pain Among Elementary School Teacher In Paron district, Ngawi Regency - Farizky Aji Nugroho; Salsabila Purnamasari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Low back pain (LBP) is one of the most common musculoskeletal disorders affecting the lumbar region of the spine and may reduce comfort and work productivity. Elementary school teachers are considered at risk of developing LBP due to prolonged static postures and workstations that may not comply with ergonomic principles. This study aimed to analyze the relationship between workstation suitability—specifically desk and chair dimensions based on anthropometric measurements—and LBP complaints among elementary school teachers in Paron District, Ngawi Regency. This study employed a quantitative approach with a cross-sectional design conducted from February to March 2025. A total of 140 elementary school teachers were included using a total sampling technique. Data were collected through anthropometric measurements to assess workstation suitability and the Oswestry Low Back Pain Disability Questionnaire (ODI) to determine the severity of LBP. The collected data were analyzed using the Chi-Square test with a 95% confidence level. The findings showed that the majority of respondents were female (71.4%) and aged 45–59 years (42.1%). Based on workstation assessment, 81.4% of respondents had ergonomically suitable workstations, while 18.6% used non-ergonomic facilities. Most respondents (83.6%) experienced minimal to mild LBP, 12.1% moderate LBP, and 4.3% severe LBP. Statistical analysis revealed a significant relationship between workstation suitability and LBP complaints (p=0.000). Non-ergonomic workstations were associated with a higher incidence and greater severity of LBP. Therefore, the implementation of ergonomic principles and proper posture education is essential to prevent LBP and to maintain teachers’ spinal health and productivity.